Simulation of pyrolysis and gasification of biomass by aspen plus - Azhar, Muhammad Aqeel (2017)
This research details the simulation of pyrolysis gasification by aspen plus software. The pyrolysis and gasification of biomass produces syngas which is a source of fuel. The temperature at which the pyrolysis was simulated is ranged between 300-450 °C. this is to maximize the production of syngas. In doing this the selection of reactors to run the simulation was done carefully and a choice of the RSTOIC, RYIELD and RGIBBS was made. This simulation is limited by the raw feed composition as different feeds have different ultimate and proximate analysis data which is of importance especially in simulating pyrolysis and gasification. This research utilizes FORTRAN codes to facilitate in calculations of conversions.